The effect of sociodemographic, socioeconomic, and health factors on healthcare utilization in cardiovascular patients in Serbia: a part of National Health Survey - Lekovic, Tamara; Janicijevic, Nikoleta; Potezica, Milos; Djonovic, Nela; Vasiljevic, Dragan; Janicijevic, Katarina; Tepavcevic, Melanija; Knezevic, Snezana; Vuckovic Filipovic, Jelena; Rastoder Celebic, Amela; Vukosavljevic, Svetlana; Mirocevic Rotolo, Maja; et al. (Frontiers in Public Health, 2025)
ObjectivesThis cross-sectional analytical study explores the predictors of the healthcare utilization in the adult population with cardiovascular diseases.MethodologyThe research was carried out as part of the fourth Serbian National Health Survey, in the period from October to December 2019, as a descriptive, cross-sectional analytical study and included the population of cardiovascular patients (N = 4,712) aged over 20 years; Descriptive and inferential statistical methods, including percentage-based structure indicators, Chi-square (χ2) tests for categorical variable differences, and prevalence ratio for examining relationships between dependent and independent variables, were used in the data analysis.ResultsThe analysis identified several significant contributors to cardiovascular healthcare utilization, emphasizing distinct and overlapping factors that impact various types of healthcare use. The chi-square test had shown that predominantly, each form of healthcare utilization was most prevalent among the 60–69 age group (general practitioner visits: 33.9%, specialist visits: 33.1%, hospitalization: 31.4%, p < 0.001). Self-assessment of general health (bad/very bad) and the presence of multiple chronic conditions (multimorbidity) were positively associated with general practitioner (PR = 1.037(1.001–1.075); p = 0.044, PR = 1.077(1.039–1.117); p < 0.001), specialist visits (PR = 1.381(1.281–1.490); p < 0.001, PR = 1.279(1.181–1.385); p < 0.001) and hospitalization (PR = 4.346(3.272–5.772); p < 0.001, PR = 2.018(1.517–2.685); p < 0.001).ConclusionSociodemographic, socioeconomic factors and some aspects of health status have a significant impact on the cardiovascular healthcare, thereby precise recommendations for facilitating appropriate healthcare utilization should be established. A top priority for academics, physicians and public health specialists is to keep emphasizing the significance of sociodemographic determinants in lowering cardiovascular complications, as well as strengthening cardiovascular healthcare.